2021
DOI: 10.1186/s12911-020-01376-8
|View full text |Cite
|
Sign up to set email alerts
|

The effects of clinical decision support system for prescribing medication on patient outcomes and physician practice performance: a systematic review and meta-analysis

Abstract: Background Clinical Decision Support Systems (CDSSs) for Prescribing are one of the innovations designed to improve physician practice performance and patient outcomes by reducing prescription errors. This study was therefore conducted to examine the effects of various CDSSs on physician practice performance and patient outcomes. Methods This systematic review was carried out by searching PubMed, Embase, Web of Science, Scopus, and Cochrane Library… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 90 publications
0
34
0
2
Order By: Relevance
“…Although the treatment decision algorithm was a major component of the initial SW tool, we concluded that the providers’, adolescents’, and parents’ discomfort with this portion of the report may preclude future implementation. Nonetheless, measurement-based care may improve depression outcomes [ 61 ] and is facilitated by computerized decision support, which may enhance compliance with clinical guidelines [ 62 ] and result in small to moderate improvements in quality of care [ 63 ]. Future iterations of SW will, instead of providing specific treatment recommendations (eg, refer for substance use treatment or follow-up in 6 weeks), gather and display information in a user-friendly way to the provider while highlighting the severity score of symptoms and discrepancies between adolescents and parents and providing reference to the current clinical guidelines to enhance clinical decision-making without being overly prescriptive.…”
Section: Discussionmentioning
confidence: 99%
“…Although the treatment decision algorithm was a major component of the initial SW tool, we concluded that the providers’, adolescents’, and parents’ discomfort with this portion of the report may preclude future implementation. Nonetheless, measurement-based care may improve depression outcomes [ 61 ] and is facilitated by computerized decision support, which may enhance compliance with clinical guidelines [ 62 ] and result in small to moderate improvements in quality of care [ 63 ]. Future iterations of SW will, instead of providing specific treatment recommendations (eg, refer for substance use treatment or follow-up in 6 weeks), gather and display information in a user-friendly way to the provider while highlighting the severity score of symptoms and discrepancies between adolescents and parents and providing reference to the current clinical guidelines to enhance clinical decision-making without being overly prescriptive.…”
Section: Discussionmentioning
confidence: 99%
“…Combining this with the development of clinical pharmaceutical activities, through visits by the pharmacist to the patients in their rooms, can also promote the re-evaluation of prescriptions, increase the acceptance of pharmaceutical interventions, and thus lead to better-adapted prescriptions for the elderly. However, the use of a computerized clinical decision support system could help us increase efficiency and relevance [34]. These new tools are currently being studied to be adapted to our practice.…”
Section: Discussionmentioning
confidence: 99%
“…Un metaanálisis que evaluó la efectividad de la PE para reducir errores de medicación y eventos adversos de los medicamentos en el ámbito hospitalario encontró una reducción significativa de los errores de medicación y las reacciones adversas a los medicamentos 18 . En AP los estudios realizados han mostrado resultados comparables en la reducción de los errores de medicación 19 , 20 .…”
Section: Receta Electrónica: Desarrollo Situación Actual Y Posibles Mejoras Para Facilitar El Seguimiento El Acceso Y La Adherencia a Losunclassified